EFFECTS OF USING SELF-REGULATION PROGRAM WITH SOCIAL SUPPORT TOWARDS DISCIPLINE BEHAVIOR IN TRAINING OF ALTHLETES PATUMWAN DEMONSTRATION SCHOOL - POEMDECH, Wichchuda; Sungthong, สังข์ทอง; Chimwong, Luxsamee (Journal of MCU Phetchaburi Review, 2024)
The purpose of this research was 1) to create a self-regulation program with social support towards the disciplined behavior of training athletes at Pathumwan Srinakharinwirot University Demonstration School, 2) to compare self-regulation programs with social support towards the disciplined behavior before and after program implementation and 3) to compare self-regulation program with social support on training discipline behavior of experimental and control group athletes. The sample group was 40 athletes from Pathumwan Srinakharinwirot University Demonstration School by using purposive sampling method. The research tool was a questionnaire on athletes' training discipline. Statistics used to analyze the data include mean, standard deviation and t-value. The results of the study showed that 1) self-regulation programs consists of factors of responsibility, patience, and punctuality, honesty and compliance with social rules can develop training discipline behavior of athletes of Pathumwan Srinakharinwirot University Demonstration School effectively with validity value of 0.60-1.00. 2) after receiving the self-regulation program, the experimental group had higher discipline behavior in training than before the experiment at the 0.05 level of significance, and 3) after participating in the self-regulation program, the disciplined behavior in practicing of the experimental group is higher than that of the control group with significantly difference at the 0.05 level of significance.